Regenerated silk matrix composite materials reinforced by silk fibres: Relationship between processing and mechanical properties. (July 2018) - Wojcieszak, Marine; Percot, Aline; Colomban, Philippe
Silk is a biocompatible material with remarkable mechanical properties. A variety of composite materials using silk as a matrix or for reinforcement have been prepared for many biological applications. However, although a range of composites containing silk have been designed, the mechanical properties achieved for the regenerated silk (solubilisation + film/matrix or fibre production) remain relatively weak (strength: 30–50 MPa). In this study, by combining the high ultimate strength (up to 1 GPa) of natural silk fibres and the chemical properties of regenerated silk, we developed a composite based on silk alone. We investigated how to improve the tensile mechanical properties of silk matrices derived from Bombyx mori silkworms by film processing and by incorporating silk fibres, either natural or degummed, that is, without the sericin coating. The structure and orientation modifications of fibroin macromolecules within the matrix were monitored by Raman spectroscopy; unexpectedly it showed that the most amorphous fibroin matrix exhibits the best mechanical behaviour. The mechanical behaviour of regenerated silk-based materials is dependent upon the temperature of evaporation and the filtration of the solution. In summary, a biocompatible composite was obtained here with distinct mechanical properties (strength >100 MPa; Young's modulus ∼2.5 GPa) which can be optimised for focused applications with silk fibres (slow degradation, skeleton of the composite) and silk matrix (fibroin molecules accessible to chemical or biophysical modification).